The Kingdom of Sriwijaya as a Form of Maritime Culture in Indonesia - Isrina Siregar; Arueng Sy Pranata; Budi Purnomo (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The introduction of maritime culture to the community needs to be improved by remembering that Indonesia is an archipelagic country. The purpose of this study is to see how the Sriwijaya Kingdom is a form of maritime culture owned by Indonesia. In addition, the author tries to see what was formed by the Srivijaya kingdom, which in its development is now a maritime culture for Indonesia. It is also known that Srivijaya is a kingdom whose life is dominant in advancing the sea area compared to daraatan. Having power in various strategic areas, it became a success that made the Sriiwjaya kingdom a great kingdom and known as the ruler of the ocean. Meanwhile, the research method used, namely a qualitative approach with data collection techniques through literature studies. The results showed that cultural factors formed stemmed from the relationship between environmental conditions and the life patterns of a group or family. Thus, it will produce a diverse culture. In the Srivijaya Kingdom itself as a large maritime kingdom, it left behind several cultures and knowledge that we can learn ranging from shipping and trade rules, government systems, and also shipping techniques.